2000
DOI: 10.2307/369190
|View full text |Cite
|
Sign up to set email alerts
|

Freedom's Web: Student Activism in an Age of Cultural Diversity

Abstract: authors used a historical approach rather than a sociological one. More over, it would be interesting to revisit Teaching in America in the future to see which of Grant and Murray's three hypotheses are proven true in regard to greater autonomy in the "precollege" teaching profession.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
23
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 0 publications
0
23
0
Order By: Relevance
“…A resurgence of progressive student activism came about in the early part of the 2010s -on the tail end of high-profile international activist movements brought to the rest of the world through the use of social media such as Arab Spring (Gerbaudo, 2012;Idle & Nunns, 2011;Muñoz & Culton, 2016) and the Occupy movement. Millennial-aged activism was a bit different from those who came before them in the 90's (Rhoads, 2000) and those of the 1960s. The activism of millennials "synthesizes the identity politics of the New Left of the 1960s and the traditional critiques of class inequality and capitalism associated with the Old Left of the 1930s" (Milkman, 2017, p. 25).…”
Section: Situating Activism Todaymentioning
confidence: 96%
See 2 more Smart Citations
“…A resurgence of progressive student activism came about in the early part of the 2010s -on the tail end of high-profile international activist movements brought to the rest of the world through the use of social media such as Arab Spring (Gerbaudo, 2012;Idle & Nunns, 2011;Muñoz & Culton, 2016) and the Occupy movement. Millennial-aged activism was a bit different from those who came before them in the 90's (Rhoads, 2000) and those of the 1960s. The activism of millennials "synthesizes the identity politics of the New Left of the 1960s and the traditional critiques of class inequality and capitalism associated with the Old Left of the 1930s" (Milkman, 2017, p. 25).…”
Section: Situating Activism Todaymentioning
confidence: 96%
“…Particularly, the word resist, related often to a culture of resistance against the Trump presidency, was used in the visual poem by Mothman and Ladybug (Figure 3), the art by Sparkle Enby (Figure 4), and the work by Leia. These pieces outright speak to resistance against an oppressive governmental system and a growing force of conservatism which like the student activists of the 1990s felt as if they had little choice but to create community and launch a countermovement (Rhoads, 2000).…”
Section: Student Leadership As Resistancementioning
confidence: 99%
See 1 more Smart Citation
“…Liberation movements of the 1980s and 1990s continued to use safe spaces as a way to exchange ideas and plan protests. Student-run organizations working to encourage campuses to divest from companies supporting apartheid and to build growing awareness concerning HIV and AIDS and the LGBTQIA community used safe spaces to share resources (Boren, 2001;Rhoads, 1998). Socioeconomic movements of the early 2000s, such as Occupy Wall Street, used safe spaces to deconstruct notions of hierarchy in building a movement.…”
Section: Movement-buildingmentioning
confidence: 99%
“…Decades of research have demonstrated higher education's critical role in promoting our nation's democratic values and cultivating civically engaged citizenry by training leaders and participants of a diverse democracy (Calderón, 2007;Hurtado, 2007;Jacoby & Associates, 2009;Longo & Gibson, 2011; The National Task Force on Civic Learning and Democratic Engagement, 2012;Rhoads, 1998;Saltmarsh & Hartley, 2011). Some higher education institutions have trained future leaders and instilled democratic ideals through structural policies around community engagement graduation requirements, curricular practices (e.g., service-learning courses), cocurricular practices (e.g., internships at the Capitol or clubs focused on providing support to the local community), or organizational cultures and institutional missions focused on serving the public good.…”
mentioning
confidence: 99%